2014
DOI: 10.1177/2050640614525152
|View full text |Cite
|
Sign up to set email alerts
|

Lack of seasonal variation in the incidence of eosinophilic oesophagitis in adolescent and adult non‐PPI‐responsive oesophageal eosinophilia midwestern US populations

Abstract: Background: Eosinophilic oesophagitis (EoO) has been associated with allergic disorders as well as aeroallergens. The current literature has shown a possible association between seasonal variation, mainly in the spring, and the incidence of EoO. However, this data was based on small population studies that did not exclude proton-pump inhibitor (PPI)-responsive oesophageal eosinophilia (PPI-ROE) in their cohort. Aim: The aim of this study was to determine if there is a seasonal variation associated with the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This observation supported the hypothesis of a relevant role for aeroallergens in the development and/or recrudescence of EoE in parallel to what happens with other atopic disorders frequently observed in these same patients. More recent research, however, failed to document such an association , with some authors documenting a higher incidence of EoE diagnosis during the fall . After collecting all the published data on this topic through a systematic search in multiple databases and subsequently analyzing the data with the aid of a random‐effects meta‐regression model of seasonal meta‐analyses, we were able to demonstrate no significant seasonal variations in the overall incidence of EoE and its flare ups.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This observation supported the hypothesis of a relevant role for aeroallergens in the development and/or recrudescence of EoE in parallel to what happens with other atopic disorders frequently observed in these same patients. More recent research, however, failed to document such an association , with some authors documenting a higher incidence of EoE diagnosis during the fall . After collecting all the published data on this topic through a systematic search in multiple databases and subsequently analyzing the data with the aid of a random‐effects meta‐regression model of seasonal meta‐analyses, we were able to demonstrate no significant seasonal variations in the overall incidence of EoE and its flare ups.…”
Section: Discussionmentioning
confidence: 63%
“…Of the remaining 46 documents retrieved for complete evaluation, 28 were excluded for the following reasons: they lacked data for calculations (20), they contained repeated or duplicated information (6), they were editorials with no original data (1), or they dealt with esophageal eosinophilia but not EoE (1). In the end, 18 studies (comprising 14 full papers and 4 abstracts ) were included in the quantitative summaries of our systematic review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Its pathophysiology is yet unknown but emerging evidence indicates that airborne and food hypersensitivity may play a key role . Some reports show a seasonal variation of incidence of EoE, suggesting a role for airborne allergens in the clinical course of EoE, but the literature remains unclear on this point . Studies have shown that 68% of pediatric EoE patients have a history of allergic disorders such as allergic rhinitis (AR), asthma, atopic dermatitis, and food allergy (FA), and that allergy testing‐directed diets in children with EoE achieved 69% resolution of the symptoms .…”
mentioning
confidence: 99%
“…Recent human data suggest that aeroallergens might be more relevant in adults and older children documenting 89% of EoE adults having aeroallergen sensitization [24] and children aeroallergen sensitization increasing with age [25]. However, there are some conflicting epidemiological data disputing the seasonal trend in EoE incidence [26,27]. …”
Section: Allergens and Dietary Therapymentioning
confidence: 99%